Analisis Hukum Terhadap Pemalsuan Dokumen Pernikahan Anak Di Bawah Umur - Atria Wati Ningsih; Ilham Abbas; Abdul Agis (Qawanin Jurnal Ilmu Hukum, 2020)
This study used a qualitative descriptive research method. The research location was in Bonto Mate’ne Village, Marusu District, Maros Regency. The type of research carried out is first, to find data by reading and examining written sources that are used as material in supporting the preparation and discussion of the writing. Second, field research (field research) is carried out through interviews, and collecting related documents. The results of this study indicate the number of data on the number of early marriages that occurred in Bonto Mate’ne Villages from 2017-2020 as many as 202 people and the factors behind the falsification of child marriage documents in the form of internal factors and external factors as well as how government efforts to prevent and reduce the occurrence of falsification of child marriage documents.